2018
DOI: 10.3390/w10040481
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Improved Water Services in Mining Regions of Developing Economies: Case Study of a Coal Mining Project in Thar Coalfield, Pakistan

Abstract: Local communities in mining regions are vulnerable to water scarcity risks caused by extensive mining and changing climate. To mitigate such risks, we adopt a non-market valuation of low income communities' preferences for improved access to water services, as an effort to develop pro-poor policies that bring long-term water security and benefits to the local people. Using data collected from 268 households from the mining site in the Thar coalfield (Pakistan), we examine the household willingness to pay (WTP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Similar results were also reported by Mezgebo and Ewnetu [120] in Nebelet town, Ethiopia. Previous studies also indicate that the increase level of household income could consequently shift the demand curve for improved water quality to the right, suggesting that the households would have better chances of maximizing utility [122,127,128]. Halkos and Matsiori [117] also reported that, as the level of income increases, people would be more willing to pay.…”
Section: Discussionmentioning
confidence: 96%
“…Similar results were also reported by Mezgebo and Ewnetu [120] in Nebelet town, Ethiopia. Previous studies also indicate that the increase level of household income could consequently shift the demand curve for improved water quality to the right, suggesting that the households would have better chances of maximizing utility [122,127,128]. Halkos and Matsiori [117] also reported that, as the level of income increases, people would be more willing to pay.…”
Section: Discussionmentioning
confidence: 96%
“…Terrestrial inputs, especially agricultural fertilizer runoffs, might be the major source of urea in the ZJB. This situation is due to the rapid development of the society and economy around the ZJB, which has led to the continuous increase in nitrogen pollutant emissions and water quality deterioration [64,65]. In particular, Potou District and Xiashan District, located on the eastern and western sides of the ZJB, brought about the continuous increase in waste water from sewage outlet discharge.…”
Section: The Concentration Variation and Sources Of Urea In Zjbmentioning
confidence: 99%
“…In addition to estimating the TCM, we analyze the visitors' responses to the hypothetical increase in entrance fees for a proposed springs restoration program following the contingent valuation method, which is a widely used method to elicit values for proposed policy interventions, such as in Aslam et al [34] and Kwak et al [35]. For simplicity and ease of administration during an onsite intercept survey, a single-bounded CV question was used.…”
Section: Methodsmentioning
confidence: 99%